SODIUM INTAKE AND RISK OF CORONARY HEART DISEASE IN THE OVERALL POPULATION AND SPECIFIC SUBPOPULATIONS - Michel Joosten; Ron Gansevoort; Hiddo Lambers Heerspink; Johanna Geleijnse; Edith Feskens; Gerjan Navis (The Korean Society of Nephrology, 2012)
Whether excess sodium intake is a risk factor for coronary heart disease (CHD) has recently been challenged, despite compelling evidence for its adverse effects on blood pressure and extracellular volume. We examined the association between sodium intake and risk of CHD in the overall population and in subgroups potentially more susceptible to the detrimental effects of high sodium intake. We included 7779 adults without previous cardiovascular diseases or cancer at baseline (1997-1998) from the observational, community-based PREVEND study. Sodium intake was estimated from two 24-h urine collections and normalized to creatinine excretion. Hypertension and N-Terminal pro-B-type Natriuretic Peptide (NTproBNP) levels above the sex-specific median were defined as predisposing factors to the adverse effects of high sodium intake. We documented 464 events, during a median follow-up of 10.5 y, There was some evidence for a trend between sodium intake and risk of CHD in the entire cohort after adjustment for CHD risk factors [Hazard ratio (HR), 1.06; 95% confidence interval (CI), 0.97-1.17 per SD increment]. Each SD increment in sodium intake was associated with a higher risk for CHD only among subjects with hypertension (n=2453; HR, 1.14; 95% CI, 1.01-1.29) and with elevated NTproBNP levels (n=3796; HR, 1.14; 95% CI, 1.02-1.28). In conclusion, a higher sodium intake was associated with an increased risk of CHD among subjects with hypertension and elevated levels of NTproBNP. These individuals might be vulnerable to the deleterious impact of high sodium intake on CHD risk.fx1